Pengaruh Persepsi Harga, Citra Merek Dan Positif (Wom) Terhadap Keputusan Pembelian Lampu Led Dan Onderdil LED (Studi Pada CV. Fiotron Pijar Jaya) - Rohmat Doni Arto; Alimuddin Rizal Riva'i (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research was shown to identify what is the influence vof price perception, brand image, positive WOM with decision purchase LED lights and LED spare parts at CV.Fiotron Pijar Jaya, in the era of competition caused by the many new brands of LED lights and spare parts at various prices. Quantitative methods are used in research. Data were taken from questionnaires that were distributed manually using statement sheets to respondents and purposive sampling methods were applied here. Multiple linear regression analysis became the model adopted to test the hypothesis. SPSS statistical software version 23 is used as a means to process data. The targeted population is potential consumers and consumers who have the potential to buy LED products CV.Fiotron Pijar Jaya. This study proves the influence of price perception, brand image, positive (WOM) at CV.Fiotron Pijar Jaya customers' purchasing decisions significantly and positively. Keywords: price, brand, WOM, purchase decission